DEBTOR INDEBTEDNESS CONTROL IN MODERN CONDITIONS AT RUP «BMZ» - D. E. Putsevich; E. E. Kozlova; O. E. Drozdova (Литьë и металлургия, 2011)
The issues of efficient control of debtor indebtedness, directed on increase of sales volume due to expansion of sale of production on credit to reliable clients are considered.